Experimental and numerical studies on freezing of droplets under effects of nanoparticles and magnetic fields - Zhang, Hui (Nanyang Technological University, 2021)
The freezing of substances on supercooled surfaces is ubiquitous in both nature and industry. Studying the freezing process of a single droplet is significant from both fundamental and practical viewpoints. Most existing studies focus on the freezing process of a single pure water droplet, and tremendous progress has been made in understanding the mechanisms involved in this process. However, the freezing behaviours of nanofluid droplets have received less attention. Furthermore, the presence of foreign particles significantly changes the properties of these systems, and these particles present new challenges for the analysis of the freezing related phenomena due to the complex particle-particle and particle-fluid interactions. This study aims to advance the understanding of the freezing dynamics of nanofluid droplets and to explore methods for controlling the freezing process of nanofluid droplets under magnetic conditions. In this thesis, the study of the freezing process of a nanofluid droplet is divided into two parts. In the first part of this study, the freezing behaviour of a nanofluid droplet is investigated both experimentally and numerically. Experimental observations have shown that the morphology of a frozen nanofluid droplet is different from that of a frozen water droplet. A flat plateau has been found to form on the top of a nanofluid droplet upon the completion of freezing, unlike the pointy tip that always appears on a frozen water droplet. This new phenomenon is attributed to the outward Marangoni flow induced by the gradient of particles along the liquid-air interface of the droplet, which can drive the liquid from the central region to the periphery of the freezing front. Experimental studies of the droplet volume, initial volumetric concentration, substrate temperature, and effects of particle size on the shape change feature of a freezing nanofluid droplet have been carried out. In addition, a scaling model has been proposed to reveal the underlying physics of this new phenomenon. Meanwhile, a regime map describing the morphologies of frozen nanofluid droplets has been developed. Furthermore, a two-dimensional numerical simulation based on the lattice Boltzmann (LB) method has been carried out. In the simulation, a multiphase solidification model is used to simulate the freezing of a droplet, and the immersed boundary method is applied to describe the small particles inside the droplet. The plateau feature can be well predicted with the LB method that has been developed in this research. The simulation results show that particles are rejected by the freezing front during the freezing process and accumulated near the freezing front. The outward movement of liquid in the central region can be observed in the simulated results for the velocity distribution. In the second parts of this study, both experimental and numerical methods are employed to investigate the effect of magnetic field on nanofluid droplets freezing. First, an active method involving the use of an applied magnetic field to control the deformation and freezing process of sessile ferrofluids droplet is developed. By changing the direction and magnitude of the magnetic field, the shape of the ferrofluid droplet can be elongated or squeezed. Consequently, the droplet freezing time can be extended and shortened under the magnetic lift and squeeze conditions, respectively. Additionally, the shape variation of a ferrofluid droplet under a magnetic field is analysed by employing the modified Young-Laplace equation. Analytical models are proposed to explain the deformation feature of the liquid ferrofluid droplet. Meanwhile, a scaling analysis is conducted to examine a relationship between the freezing time and the frozen droplet height. Secondly, numerical and scaling analyses of the freezing process for ferrofluid droplets under magnetic field effects are performed. A new LB model is proposed and the model takes magnetic force and stress into consideration. It is found that the effect of the magnetic field gradient is much larger than that of the magnetisation. Scaling models have been developed to describe the acceleration of the freezing front in a ferrofluid droplet near the completion of freezing. The simulated morphologies of ferrofluid droplets agree well with the experimental snapshots.